Hyperacute versus Subacute Coiling of Aneurysmal Subarachnoid Hemorrhage a Short-term Outcome and Single-Center Experience, Pilot Study - Ibrahim Ali, Abdulrahman Mostafa; Ashmawy, Ghada Abdel Hady Ossman; Eassa, Ayman Youssef Ezeddin; Mansour, Osama Yassin (Frontiers in Neurology, 2016)
Background: After the initial SAH, rebleeding is the major cause of morbidity and poor outcome which is maximal in the first 24 hours. We supposed that coiling of ruptured intracranial aneurysms within 24 hours of SAH is related to improved clinical outcome compared with coiling 24 hours after aneurysmal SAH. Objective: we examined whether coiling ruptured aneurysms within 24 hours of aneurysmal subarachnoid hemorrhage is associated with better early 24 hours’ and late 30 days outcome. Method: This prospective study was carried on 30 patients with aneurysmal subarachnoid hemorrhage presenting to the Alexandria University Hospital and Insurance Main Hospital during the period from February 2013 till May 2104. They were divided into two groups: Group I (10 patients treated within 24 hours of presentation) and Group II (20 patients treated after 24 hours of presentation). Time Interval from presentation to treatment were 78.60 and 10.60 hours for subacute and hyperacute group respectively. All patients treated with endovascular coiling. Change between admission and immediate post-operative World Federation of Neurosurgeons classification Scale was measured for early outcome while remote outcome was measured by modified Rankin Scale at 30 days follow up. Results: There was a clinical improvement regarding early 24 hours’ outcome (weighted by post-operative WFNS grade) and on late 30 days outcome (weighted by Modified Rankin Scale Score) in the group managed within 24 hours versus who were treated after 24 hours (p=0.049 and 0.024, respectively). There was a significant decrease in the incidence of clinical rebleeding detected by post-operative Computed Tomography (CT) of the brain in patients undergoing aneurysm treatment within 24 hours (p=0.029). Conclusion: The study affirms evidence that management of ruptured intracranial aneurysms within 24 hours of SAH is associated with better immediate and short-term clinical outcome.